The Clinical Profile of Patients with Chronic Wounds at Dr. Soetomo General Hospital 2015-2020 - budirahmadina, nurvania aurellia; perdanakusuma , david sontani; ervianti, evy; saputra, iswinarno doso (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2023)
Background: Wounds that have lasted a long time due to failure to continue the normal healing process can be called chronic wounds. Chronic wounds occur due to multiple factors. There are problems that are often found in chronic wounds, such as the presence of exudate, necrotic tissue, and bacteria. The incidence of chronic wounds is closely related to the high cost of treatment and impaired quality of life. Prompt wound management is needed to optimize wound healing. Purpose: To determine the profile of chronic wounds in patients treated by the Department of Plastic Surgery Dr. Soetomo General Hospital Surabaya from 2015 – 2020. Methods: The data were obtained from patients medical records through total sampling technique, which consist of age,   gender, past medical history, clinical features, diagnosis, management, and outcome. Result: This study involved 53 patients, dominated by male patients (70%) aged 46-65 years old (34%). The patient's history showed that most patients suffered from type 2 diabetes (22%). The problem that often occurs is the presence of exudate which is mostly diagnosed with pressure ulcers (40%). All patient get wound bed preparation and the patient's outcome was dominated by recovery (72%). Conclusion: There are several factors affecting wound healing and prompt wound management are important to improving the outcomes.